Local Potential Optimization: A SWOT Review Of The Traditional Moke Beverage Industry In Sikka Regency - Eugenius Besli; Hersanius Kurnia Peong (Pusat Penelitian dan Pengabdian Masyarakat Politeknik eLBajo Commodus, 2024)
This study aims to analyze the moke cottage industry with the SWOT technique. The research was conducted by in-depth interviews with the main informants of the moke business in Nele and Watu Gong villages, Sikka Regency. The results of the interviews were analyzed using the SWOT technique. The results of the study indicate that the moke cottage industry has the opportnity for being developed mainly due to the support of the availability of raw materials. However, it should be noted that the moke business actor has limited resources so that they failed to analyze various aspects related to the production and marketing of moke. There needs to be a collaborative effort between moke businesses, investors and local governments to develop moke home industry in Sikka Regency.